2002
DOI: 10.1073/pnas.142125899
|View full text |Cite
|
Sign up to set email alerts
|

Overt female mate competition and preference for central males in a lekking antelope

Abstract: In mammals, there exists only scant evidence of female mate choice in species mating on arenas, so-called leks. This has led to hypotheses of lek evolution that are based on benefits to females from reduced harassment by males, low predation risk, or improved availability of scarce nutrients. Here I report that female topi antelopes (Damaliscus lunatus) compete aggressively for matings with preferred males on central lek territories. Females fight at higher rates and more likely disrupt mating attempts of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(91 citation statements)
references
References 28 publications
0
89
1
1
Order By: Relevance
“…3). Similarly, in some polygynous ungulates where males initially compete intensely for females, females that have entered estrus and need to mate rapidly compete for the attentions of defending males (57,58). Several studies of species where both sexes make large investments in their offspring have shown that the relative intensity of reproductive competition in the two sexes can be changed by manipulating resource availability and reversing sex differences in PRR (59,60).…”
Section: Sexual Selection In Femalesmentioning
confidence: 99%
“…3). Similarly, in some polygynous ungulates where males initially compete intensely for females, females that have entered estrus and need to mate rapidly compete for the attentions of defending males (57,58). Several studies of species where both sexes make large investments in their offspring have shown that the relative intensity of reproductive competition in the two sexes can be changed by manipulating resource availability and reversing sex differences in PRR (59,60).…”
Section: Sexual Selection In Femalesmentioning
confidence: 99%
“…Certainly, the vigorous repetition of a display can serve other functions, such as repelling rivals, or simply increasing the likelihood of attracting a female, but to the extent that repetition is energetically costly, or to the extent that repetition exposes the signaler to danger or risk of retaliation, it becomes a way in which the quality of males can be compared. In addition, females may be able to assess vigor by observing male fighting and similar forms of competition, by indirectly detecting the outcome of male-male competition, or by inciting male competition and selecting the winner (Cox and LeBoeuf, 1977;Byers et al, 1994;Bro-Jorgensen, 2002). In many lek-breeding species, females prefer to mate with males that occupy territories at the spatial centre of the lek (Hoglund and Lundberg, 1987;Apollonio et al, 1992;Kokko et al, 1999;Isvaran and Jhala, 2000;Bro-Jorgensen and Durant, 2003).…”
Section: Motor Performance As Vigormentioning
confidence: 99%
“…Opinions on ungulate female choice are still divided because males often try to restrict female movements and thereby might constrain female choice (Clutton-Brock and McAuliffe 2009;Bro-Jørgensen 2011), but nevertheless, there is strong evidence for ungulate female mate choice, including in fallow deer (Komers et al 1999;Bro-Jørgensen 2002;Byers and Waits 2006;Bowyer et al 2011;Farrell et al 2011;Dunn et al 2012). In addition, reports of polyandry in cervids are very rare (Endo and Doi 2002;Vanpé et al 2009).…”
Section: Communicated By Ke Ruckstuhlmentioning
confidence: 99%